ChemInform Abstract: A Mild Method for Indium(III)‐Catalyzed 1, 4‐Hydrosilylation of α, β‐Enone Esters with Triethylsilane and Trifluoroacetic Acid. Issue 2 (9th January 2013) - Xing, Ping; Zang, Wei; Huang, Zuo‐gang; Zhan, Yue‐xiong; Zhu, Chuan‐jun; Jiang, Biao
Abstract α‐Keto esters of type (I) undergo an efficient stereoselective hydrosilylation give moderate yields of the desired α, β‐unsaturated esters (III).